2017
DOI: 10.1016/j.athoracsur.2016.05.106
|View full text |Cite
|
Sign up to set email alerts
|

A Papillary Fibroelastoma Involving Aortic and Pulmonary Valves: Findings on Multimodality Imaging

Abstract: Cardiac papillary fibroelastoma, a rare entity, is the second most common benign primary cardiac tumor. Commonly involving the cardiac valves, this entity is increasingly diagnosed using different imaging modalities. We present a rare case of simultaneous involvement of both the aortic and pulmonary valves in an asymptomatic patient who underwent different imaging modalities, including transthoracic and transesophageal echocardiography, nongated and gated computed tomography, and magnetic resonance imaging. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Most tumors occur as solitary lesions on the left side of the heart and are ≤1.5 cm in diameter [1,14,1719]. The clinical presentation of cardiac papillary fibroelastoma varies from asymptomatic to severe embolic complications [18]. The most common symptoms are cerebral embolic events and chest pain [1,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most tumors occur as solitary lesions on the left side of the heart and are ≤1.5 cm in diameter [1,14,1719]. The clinical presentation of cardiac papillary fibroelastoma varies from asymptomatic to severe embolic complications [18]. The most common symptoms are cerebral embolic events and chest pain [1,20].…”
Section: Introductionmentioning
confidence: 99%
“…If an extensive resection is needed, valve replacement may be necessary [14]. Furthermore, the long-term postoperative prognosis is excellent with low recurrence rate [1,11,12,18]. …”
Section: Introductionmentioning
confidence: 99%
“…Cardiac MRI can be useful in ascertaining signal characteristics but it can have difficulty in identifying points of attachment, which can be better assessed with electrocardiographically gated CT and TEE. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Cardiac MRI can be useful in ascertaining signal characteristics but it can have difficulty in identifying points of attachment, which can be better assessed with electrocardiographically gated CT and TEE. 14 In a meta-analysis of 725 CPF cases conducted in 2003, the authors postulated that tumor mobility was the only independent predictor of CPF-related death or nonfatal embolization. 1 However, a later study found that the echocardiographic characteristics of CPFs were not significantly associated with CVA.…”
Section: Video Highlightsmentioning
confidence: 99%
“… 9 However, involvement of the pulmonary valve, and even simultaneous involvement of both aortic and pulmonary valves, has been reported. 10 Nonvalvular PFEs represent 15% of all cases reported 8 and can arise from the endocardium of both the left and right ventricles (septum and papillary muscles), atria (septum, appendages, Eustachian valve, and Chiari network), and the intimal surface of coronary artery ostia. Most nonvalvular PFEs originate in the left ventricle, with an incidence of approximately 9%, favoring the interventricular septum.…”
Section: Discussionmentioning
confidence: 99%